Developing and Piloting a Computerized Adaptive Test for a Culturally Appropriate Measure of Adaptive Behavior. (April 2022) - Chen, Mo; Nah, Yong-Hwee; Waschl, Nicolette; Poon, Kenneth; Chen, Ping
Culturally bounded in nature, adaptive behavior is the degree to which a person meets the requirements of personal independence and social responsibilities. This study aimed to develop a computerized adaptive test (CAT) of a culturally appropriate adaptive behavior measure (i.e., the Activities and Participation Rating Scale [APRS]) in the Singapore context for children aged 7 to 12 years, that is, the CAT-APRS-Primary. In Study 1, an item bank consisting of 310 adaptive skills was developed and piloted among 56 caregivers. In Study 2, the refined 310 items were calibrated using Rasch analysis among 352 caregivers. After the removal of five poor items based on the Rasch analysis, the finalized 305 items were used for the CAT development, with these items showing good Rasch person and item fit statistics. Preliminary utility of the CAT-APRS-Primary was established, with participants completing 24 items on average. Limitations and implications for future research were discussed.